PENGARUH FACEBOOK ADDICTION TERHADAP KEBIASAAN BELAJAR SISWA - Sitanggang, Dahlia Veronika (2013)
This study is based on the phenomenon that indicates not optimal study habits of students in school due influenced by Facebook. The purposes of these researches are: (1) to find out Facebook addiction pictures of the eighth grade students in SMP Negeri 10 Bandung, (2) to find out the images of the eighth grade students learning habits in SMP Negeri 10 Bandung, and (3) to find out the influence of Facebook addiction access with 8th grade students learning habits in SMP Negeri 10 Bandung. This study uses a quantitative approach with descriptive methods. The sampling of this research as much as 341 students sampling population. The results showed that: (1) the addiction of Facebook access for 8th grade students in general are in the medium category, (2) the habits of study of 8th grade student in general are in the low category, and (3) the implications for guidance and counseling arranged in the form of and tutoring program for improving study habits of students who have Facebook addiction. Based on the results of the study are: (1) the school is able to work together (between school personnel) in an effort to improve the study habits of students who have Facebook addiction (2) BK teachers conduct a needs analysis (needs assessment) depth as a cornerstone in developing and implementing the guidance program learning to enhance students 'learning habits, and (3) researchers can further develop the programs that have made a hypothetical experiment to analyze the effectiveness of the tutoring program in an effort to improve students' learning habits. Keywords: Study Habits, Facebook Addiction, Tutoring